Hypersensitive meta-crack strain sensor for real-time biomedical monitoring - Lee, Jae Hwan; Kim, Yoon Nam; Lee, Junsang; Jeon, Jooik; Bae, Jae Young; Lee, Ju Yong; Kim, Kyung Sub; Chae, Minseong; Park, Hyunjun; Kim, Jong Hyoung; Lee, Kang Sik; Kim, Jeonghyun; et al. (Science Advances, 2024)
Real-time monitoring of infinitesimal deformations on complex morphologies is essential for precision biomechanical engineering. While flexible strain sensors facilitate real-time monitoring with shape-adaptive properties, their sensitivity is generally lower than spectroscopic imaging methods. Crack-based strain sensors achieve enhanced sensitivity with gauge factors (GFs) exceeding 30,000; however, such GFs are only attainable at large strains exceeding several percent and decline below 10 for strains under 10−3, rendering them inadequate for minute deformations. Here, we introduce hypersensitive and flexible “meta-crack” sensors detecting infinitesimal strains through previously undiscovered crack-opening mechanisms. These sensors achieve remarkable GFs surpassing 1000 at strains of 10−4 on substrates with a Poisson’s ratio of −0.9. The crack orientation–independent gap-widening behavior elucidates the origin of hypersensitivity, corroborated by simplified models and finite element analysis. Additionally, parallel mechanical circuits of meta-cracks effectively address the trade-off between resolution and maximum sensing threshold. In vivo real-time monitoring of cerebrovascular dynamics with a strain resolution of 10−5 underscores the hypersensitivity and conformal adaptability of sensors.
Keywords: Biomedical monitoring; Complex morphology; Gage factors; Imaging method; Property; Real time monitoring; Real- time; Shape-adaptive; Spectroscopic imaging; Strain sensors; Animals; Biomechanical Phenomena; Biosensing Techniques; Finite Element Analysis; Humans; Monitoring, Physiologic; Stress, Mechanical